Information anxiety - Wurman, Richard Saul, 1935- 4 0 16; 5 (New York : Doubleday, 1989)
On t.p.: . . .is produced by the ever -widening gap between what we understand and what we should understand. It is the black hole between data and knowledge, and it happens when information doesn't tell us what we want or need to know.
Bibliography: p. 339-348.
Wilson's Public Library
Adult;Adult
Keywords: 2 -- 0; 6; Communication.;Mass media.;Mass media; 20; 2